The Influence of STEAM Integrated PjBL Learning Model on Communication Skills, Critical Thinking Skills and Problem-Solving Skills of Students in Biology Subject - Iin Anugrahsari; Nurhayati B Nurhayati B; Syamsiah Syamsiah (Jurnal Penelitian Pendidikan IPA, 2025)
21st century education requires students to be more independent in learning. However, the integration of Project Based Learning (PjBL) with STEAM has not been widely explored. This study aimed to examine the effect of the STEAM-integrated PjBL model on students’ communication, critical thinking, and problem-solving skills. Using a quasi-experimental design with a pretest-posttest control group, the experimental class was taught using PjBL-STEAM, while the control class used Direct Instruction. Results showed that the experimental class had a greater improvement than the control. In critical thinking, 16 of 33 students in the experimental class were in the very high category, compared to only 3 in the control class. In problem-solving, 3 students in the experimental class were in the very high category and 27 in the high category, while the control class had none in the very high and only 12 in the high category. Observation of communication skills showed 30% of the experimental class were in the very high oral category and 18% in written, while only 3% in the control class reached this level. In conclusion, the PjBL-STEAM model positively influences students’ communication, critical thinking, and problem-solving skills.